ANALISIS PENGATURAN NETRALITAS APARATUR SIPIL NEGARA (ASN) PADA PENYELENGGARAAN PEMILUKADA DALAM PERSPEKTIF PERATURAN PERUNDANG-UNDANGAN - YOGA TRIWANDA; Dessy Artina; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The electoral system is a mechanism or procedure for determining pairs of candidates who areentitled to occupy the position of regional head/deputy regional head. Today, there are several issues thatoften arise and become a concern that offends the local election. One of them is the politicization ofASN, which of course affects the quality of ASN performance. ASN as servants of the state haveobligations that must be fulfilled in public service, in fact they are often contaminated by politicalinterests. Various regulations have been issued, but this has not yet become a concrete solution. Theneutrality of ASN does not recur in the lead-up to and implementation of elections. The purpose ofwriting this research is to find out the condition of ASN neutrality in the 2020 regional election in Riauand to find out the material strengthening of the regulation of ASN neutrality in laws and regulations.The type of research used by researchers is normative law. Normative legal research is conductingresearch on legal principles starting from certain legal principles, by first identifying the legal principlesthat have been formulated in certain laws. The data sources used are primary data, secondary data,tertiary data, the data collection technique in this study is normative juridical, the data used is libraryresearch.The results of this study examine and analyze the rules governing the neutrality of ASN based onLaw no. 5 Year 2021that every ASN is impartial from any form of influence and does not favor theinterests of anyoneand PP No. 94 of 2021 that there are still some deficiencies governing the neutrality ofASN, as well as the existence of PPthe there are still many experiencing deficiencies and the rules havenot answered the phenomenon of ASN neutrality in Indonesia.Laws and regulations regarding ASN neutrality need to be adjusted to the needs anddevelopments in the technological age because of course it is a new challenge in perfecting laws andregulations, especially regarding ASN neutrality so that cases that occurred before, during and after theELECTIONS do not happen again. In order to achieve the desired law (right to be established) theestablishment of strengthening the regulation of ASN Neutrality by regulating the authority of KASN tosupervise staffing officials if they commit violations in the merit system-based staffing developmentprocess in Law No. 5 of 2014 concerning ASN neutrality, and PP No. 94 of 2021 concerning CivilServant Discipline prohibits lending property state for the campaign needs of one of the candidate pairs,and regulate ASN ethics on social media in terms of acting and other rules deemed necessary, so thatASN Neutrality can really be regulated in detail to guarantee legal certainty.Keywords : Analysis, Neutrality, ASN, Regulations